SPECIFICS OF THE LEGAL STATUS OF THE MORDVINIAN PEOPLE IN THE HISTORY OF THE RUSSIAN STATE - Sushkova, Iuiia (Revista Inclusiones, 2020)
The rationale of the study is the uniqueness of the system of the multi-national and multi-confessional Russian state. Peoples’ inclusion into a single state legal framework determined the need to develop a relevant ethnic legal policy. In this regard, this paper is aimed at articulating the historical and legal status of the Mordvinian people within the Russian state. The paper discusses the key aspects of the Mordva status under the Russian law. It looks into 16th–18th centuries regulations regarding nonRussians that determined the specifics of their adaptation within Russia. The study mainly employed the historical method, which made it possible to historically and legally assess laws and regulations that reflect specifics of Mordva legal status in the 16th–18th centuries. The paper has a practical value for improving the legislation for inter-ethnic relations and strengthening the foundations of federalism as the key characteristic of the Russian state.